Determinants of growth and inflation in Southern Mediterranean countries - Leonor Coutinho (Center for Social and Economic Research (CASE), 2012)
Despite significant economic reforms in many Southern Mediterranean EU neighbour countries, their growth performance has on average been subdued. This study analyses the differences in growth performance and macroeconomic stability across Mediterranean countries, to draw lessons for the future. The main findings are that Southern Mediterranean countries should benefit from closer ties with the EU that result in higher levels of trade and FDI inflows, once the turbulence of the 'Arab Spring' is resolved, and from the development of financial markets and infrastructure. They will also benefit in keeping inflation under control, which will depend in great part on their ability to maintain fiscal discipline and sustainable current accounts. One of the main challenges for the region will be to implement structural reforms that can help them absorb a large pool of unemployed without creating upward risks to inflation.
Keywords: O40; F15; F43; E61; 330; Growth; EU neighborhood policy; Trade; FDI; Financial Development; Inflation; Wirtschaftswachstum; Inflation; EU-Nachbarstaaten; Internationale Wirtschaftsbeziehungen; Regionale Wirtschaftsintegration; Westasien; Nordafrika; Mittelmeerraum; EU-Staaten